2022
DOI: 10.1371/journal.pone.0268299
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of thoracic endometriosis in the pleural cavity

Abstract: Background Thoracic endometriosis-related pneumothorax is a secondary spontaneous pneumothorax caused by thoracic endometriosis. Diaphragmatic endometriosis is well-studied, but visceral and/or parietal pleural lesions are not. Although surgery is an effective treatment, postoperative recurrence rates are unsatisfactory probably due to inadequate understanding of underlying pathophysiology. We aimed to clarify the clinicopathological features of thoracic endometriosis. Methods In total, 160 patients who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Diaphragmatic endometriosis as visualized by laparoscopy was present in 89% of patients with catamenial pneumothorax [21], which is supposed to be a direct sign of the thoracic endometriosis syndrome. It should be noted that diaphragmatic pleural involvement was noted in 100% of patients with thoracic endometriosis [40]. Wetzel et al [24] reported better treatment outcomes in patients who received Video-Assisted Thoracoscopy (VATs).…”
Section: Discussionmentioning
confidence: 99%
“…Diaphragmatic endometriosis as visualized by laparoscopy was present in 89% of patients with catamenial pneumothorax [21], which is supposed to be a direct sign of the thoracic endometriosis syndrome. It should be noted that diaphragmatic pleural involvement was noted in 100% of patients with thoracic endometriosis [40]. Wetzel et al [24] reported better treatment outcomes in patients who received Video-Assisted Thoracoscopy (VATs).…”
Section: Discussionmentioning
confidence: 99%
“…They reported 11,599 women (13-53 years), of whom 4501 (38%) were referred for surgery, but only 813 with catamenial pneumothorax, and an annual person-base incidence of 0.22/100,000 population, despite their female specific peak around 40 years. Nevertheless, Ochi et al [28] published a histopathological study collected from a single-center cohort in Tokyo. Among 435 women (15-55 years) operated on for SP, they diagnosed 160 (38%) with proven TES, which is similar to Alifano's findings.…”
Section: Discussionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/jcm12175578/s1, Table S1: Estimated annual incidence of SP and TES in France, England and Japan. References [19,[25][26][27][28] are cited in Supplementary Materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%